The organizational climate and its relationship with the teachers’ performance - Díaz Tello, Erlith (2018)
Education in the most powerful weapon that exist to change the society. It is that intangible instrument that permit the human being stand out in this competitive world where knowing only how to read and write is not enough. To achieve this,  it is necessary an education in organizational quality and highly qualified teachers that permit their students analyze and seek solution to the situations of their environment. The characteristics of a good organizational climate and how it influences in the good teachers’ performance are fundamental topic to achieve the educational quality of our educational institutions, therefore, the quality principles should be developed in order to permit perceive the strengths and weaknesses.